Institutional Transformation of Pesantren in the Era of Disruption: Analysis of Structural Problems and Development Strategies Based on Local Wisdom - Harto, Budi; Aprison, Wedra (STIT Ahlussunnah Bukittinggi, 2025)
This study analyzes the dynamics of institutional transformation in Islamic boarding schools in Indonesia in the face of the digital disruption era, which is characterized by rapid social, technological, and educational changes. Using a systematic literature review of 45 articles indexed in Scopus and SINTA 1-2 for the period 2018-2024, this study identifies three main structural problems that hinder the transformation of Islamic boarding schools: cultural resistance to innovation, limited institutional capacity, and dualism in the education system. The findings were analyzed through the triangulation of three theoretical frameworks: Talcott Parsons' structural-functional theory, Douglass North's institutional theory, and Jack Mezirow's Transformative Learning theory. The synthesis resulted in a holistic transformation model based on local wisdom that integrates five strategic dimensions: leadership transformation, curriculum, pedagogy, management, and external networks. This model emphasizes the importance of Kyai leadership as Norm Entrepreneurs, the integration of traditional values with modern innovation, and the continuous strengthening of organizational capacity.